Defending the Majesty of Islam: Indonesia's Front Pembela Islam (FPI) 1998-2003 - Jajang Jahroni (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
Indonesia's reformation in 1998 provided an opportunity for the resurgence of Islamic fundamentalist movements. This can be seen from the proliferation of newly formed organisations which aim at either establishing an Islamic state or applying Islamic law. The emergence of these organisations is closely related to the spirit of reformation, where people seem to be free to express their feelings. Almost every day one can see people gathering at the House of Representatives in Senayan, Jakarta, in order to express their aspirations to the members of parliament.DOI: 10.15408/sdi.v11i2.601